1995
DOI: 10.3109/08037059509077585
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Hypertriglyceridemic Rat: A New Animal Model of Metabolic Alterations in Hypertension

Abstract: Hereditary hypertriglyceridemic rats (hHTg) were developed as a new genetic model for the study of relationships between blood pressure (BP) and metabolic abnormalities. This strain has been produced by selective inbreeding from Wistar rats according to the rise of plasma triglycerides induced by a high-sucrose diet. Though hHTg rats display hypertriglyceridemia, impaired glucose tolerance, hyperinsulinemia, insulin resistance and increased BP even without nutritional stimuli, high sucrose feeding further aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…The hHTg rat strain was selected solely on the basis of a plasma Tg response to a high monosaccharide diet [5]. Thus, the subsequent finding [4] of moderate hypertension in the model, in the context of previous data on the IR syndrome [2], strongly suggested that a common genetic basis could underlie the dyslipidaemia and hypertension. It was therefore quite surprising to observe that neither the chromosome 4 nor the chromosome 8 Tg QTLs had any effect on BP despite the very powerful effects on Tg concentration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The hHTg rat strain was selected solely on the basis of a plasma Tg response to a high monosaccharide diet [5]. Thus, the subsequent finding [4] of moderate hypertension in the model, in the context of previous data on the IR syndrome [2], strongly suggested that a common genetic basis could underlie the dyslipidaemia and hypertension. It was therefore quite surprising to observe that neither the chromosome 4 nor the chromosome 8 Tg QTLs had any effect on BP despite the very powerful effects on Tg concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The derivation of the hHTg strain is described elsewhere [4]. The rats used in this study were from a colony set up at the Institute of Experimental Endocrinology in Bratislava, Slovakia in 1993 from breeding pairs provided by Dr. Vrana, and subsequently maintained by sibling mating.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations